Recurrence of venous thromboembolism in patients with recent gestational deep vein thrombosis or pulmonary embolism: Findings from the RIETE Registry - Barillari G; Londero AP; Brenner B; Nauffal D; Muñoz-Torrero JF; Del Molino F; Moustafa F; Madridano O; Martín-Martos F; Monreal M; RIETE Investigators; Bosevski M; et al. (Elsevier, 2016)
Introduction: The aim of this study was to investigate the recurrence rate of venous thromboembolism (VTE) and the prevalence of major bleeding or death in patients with previous VTE in pregnancy and puerperium. Risk factors for VTE recurrence were also assessed. Materials and methods: We evaluated a cohort of patients enrolled in the international, multicenter, prospective Registro Informatizado de la Enfermedad Trombo-Embólica (RIETE) registry with objectively confirmed VTE. Results: In the registry, 607 women were presenting with VTE that occurred during pregnancy or puerperium. The 2-year VTE recurrence rate was 3.3% (CI: 95 1.5-5.0%) and the recurrent VTE incidence rate was 2.28events/100 patients-year. Among the 16 cases of VTE recurrence 11 cases appeared during drug treatment while only five cases were diagnosed after therapy discontinuation. No significant difference was found in treatment duration among these two subgroups of VTE recurrence cases and women without recurrence. Furthermore, the use of thrombolytics and inferior vena cava filter in initial treatment was associated to an increased risk of VTE recurrence. Conclusions: The current study provides new insights on VTE recurrence rate in patients with deep vein thrombosis (DVT) or pulmonary embolism (PE) that occurred in pregnancy or postpartum period. These findings can contribute to risk assessment of thrombotic burden, thereby allowing for better decision making regarding antithrombotic management in this clinical setting.
Keywords: Deep-vein thrombosis; Major bleeding; Pregnancy; Puerperium; Pulmonary embolism; Recurrent thromboembolism